ETIKA PEREMPUAN DI RUANG PUBLIK : PEMAHAMAN TEMATIS-KORELATIF HADIS-HADIS TENTANG PEREMPUAN - Febriyeni Febriyeni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
In the Islamic point of view, there is no prohibition for women to play a role in the publik scene. Even since the time of Rasulullah SAW, the role of women in the publik scene has occurred. Women at the time of the Prophet were present in the study attended by men, actively participating in spreading the religion of Islam, even women also participated in wars, treated and took care of sick, injured soldiers and provide for their eating and drinking needs. This shows the association of men and women in publik spaces is allowed. However, this does not mean eliminating barriers between men and women, and forgetting the restrictions of sharia prevailing in meetings that men and women participate in. Therefore, it is necessary to know the ethics for women when in the publik scenes, according to the guidance of the Qur'an and Sunnah. This research uses library research method by reviewing the verses and hadis that discuss the issue of women ethics while in publik scenes.